Textural Properties and Adsorption of Dyes onto Carbons Derived from Cotton Stalks - Amina A. Attia; Abdel-Nasser A. El-Hendawy; Soheir A. Khedr; Th. El-Nabarawy (Adsorption Science & Technology, 2004)
Non-activated carbon ‘C’, zinc chloride-activated carbon ‘Z’ and steam-activated carbon ‘S’ were prepared from cotton stalks available as an agricultural waste. These carbon adsorbents were investigated to determine their texture and their potential for dye adsorption. Cotton stalks after chopping, washing and drying were also investigated as an additional adsorbent, designated ‘P’. The textural properties (surface area and porosity) of the sorbents were determined from the low-temperature adsorption of nitrogen at −196°C by carefully analyzing their nitrogen adsorption isotherms. The adsorption of Methylene Blue (MB) and Congo Red (CR) at 30, 40 and 50°C was investigated via kinetic and equilibrium adsorption measurements. Activated carbons ‘Z’ and ‘S’ exhibited high surface areas and high total pore volumes and possessed high dye uptakes. Non-activated carbon ‘C’ possessed a lower but satisfactory dye uptake while the raw material ‘P’ exhibited the lowest dye uptake. The adsorption of MB and CR was controlled by pore diffusion and followed first-order kinetics. The adsorption of the two dyes decreased with increasing adsorption temperature. The adsorption of both MB and CR was associated with a decrease in ΔG but with an increase in ΔS.